2018
DOI: 10.1002/oby.22124
|View full text |Cite
|
Sign up to set email alerts
|

High Fat and Sugar Consumption During Ad Libitum Intake Predicts Weight Gain

Abstract: ObjectiveTo determine how macronutrients accompanying high-EnDen foods affect energy intake and weight gain.Methods214 subjects(130 males, BMI:32 ± 7 kg/m2) ate ad libitum for 3-days. Food intake was expressed as mean daily intake(kcal) and percentage of weight-maintaining energy needs(%WMEN). EnDen was expressed as the ratio of intake(kcal) to food weight(g). Food choices were expressed as absolute and percent intake(kcal), categorized as high(HF; ≥45% kcal) or low in fat(LF; <20% kcal) and further categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…OF by 40% above baseline energy needs may be an insufficient stimulus to reveal adaptive responses that predict future weight change. However, our finding is in agreement with two prior investigations that, despite providing unlimited access to 40 participant‐selected foods via vending machine technology , also found that total ad libitum EI was not associated with weight gain over 6 months to 11 years of follow‐up . Interestingly, consumption of specific foods (i.e., those high in fat and simple sugars) was correlated with weight gain over time .…”
Section: Discussionsupporting
confidence: 92%
“…OF by 40% above baseline energy needs may be an insufficient stimulus to reveal adaptive responses that predict future weight change. However, our finding is in agreement with two prior investigations that, despite providing unlimited access to 40 participant‐selected foods via vending machine technology , also found that total ad libitum EI was not associated with weight gain over 6 months to 11 years of follow‐up . Interestingly, consumption of specific foods (i.e., those high in fat and simple sugars) was correlated with weight gain over time .…”
Section: Discussionsupporting
confidence: 92%
“…The findings are consistent with the theoretical and scientific literature indicating that two or more palatability‐inducing ingredients at moderate to high levels may be sufficient to induce hyper‐palatability . Our findings expand on the existing literature by highlighting the role of sodium in enhancing palatability, an ingredient that was key in two of our three clusters, as prior research has primarily focused on combinations of fat and sugar or fat and carbohydrates . In addition, our findings lend further support to the existing literature that has identified fat and sugar as important ingredients that synergistically enhance food palatability .…”
Section: Discussionsupporting
confidence: 89%
“…For example, several small experimental studies in humans have demonstrated that a combination of fat and sodium (FSOD) may synergistically enhance food palatability and increase consumption by up to 30% (16,17). Others have reported that combinations of fat and simple sugars (FS) may heighten preference and palatability (18)(19)(20)(21) and that consumption of high fat and high sugar may lead to future weight gain (22). Findings from the behavioral literature are supported by the findings of a recent neuroimaging study in humans that reported supra-additive effects of combining fat and carbohydrates; foods with fat-carbohydrate combinations were more efficient in activating brain reward neural circuitry than foods with either fat or carbohydrates alone (23).…”
Section: Introductionmentioning
confidence: 99%
“…We found that household use of cooking oil was positively associated with female BMI, reinforcing the idea that consuming more energy‐dense foods promotes weight gain . When available, Tsimane’ will use oil to cook plantains, rice, dried meat, and fish in order to enhance their flavor and texture.…”
Section: Discussionsupporting
confidence: 63%